The Rule of Law and the Populist Radical Right in Modern Europe: From Interpretation to Current Challenges - Aalio, Oona (My University, 2020)
The principle of the rule of law has a long tradition in Europe where it has commonly been understood as both a political and a legal principle. The rule of law can be defined in different ways, varying from strictly formal to more substantive definitions. The principle of the rule of law has been a recurring theme of the discussions in Europe during the recent years, due to the political developments that have led to the slides of some of the former liberal democracies into different levels of authoritarianism. The aim of this study is to determine how the rule of law can be defined and what could be determined as forming its legal agenda in the context of modern Europe. In light of the recent global developments and the rise of the populist radical right parties and leaders, the rule of law principle is relevant and current. Therefore, it serves a purpose to determine the different legal elements included in the principle. The starting point for this analysis is the norms and statements of the European Union and the Council of Europe. The second aim is to determine the common characteristics and legal agenda of the populist radical right parties in Europe. These parties have gained support in several European states, and their victories in parliamentary elections have led to systemic threats to the realisation of the rule of law principle. In this study the focus will be on Hungary and Poland. The final aim of this study is to assess if the legal agendas of the European rule of law and the populist radical right parties clash. The method used in this study is multidisciplinary. In the first part of this study, which focuses on determining the legal definition of the European rule of law, the method is legal dogmatic and the main sources consist of legislation, case law, and legal and political literature. The method used in the rest of the study, when determining the possible clash between the two legal agendas, is legal dogmatic, legal sociological and political sociological. This part of the study is based on legal, legal sociological, political sociological and anthropological literature. To summarise the findings of this study, it can be concluded that there is a consensus between the European Union and the Council of Europe on the core definition and the legal agenda of the rule of law principle. This definition of the rule of law is substantive. The legal agenda of the populist radical right parties includes an understanding of the rule of law that is different from the broader European interpretation. In this study, the legal agenda of the populist radical right is assessed mainly from the perspective of liberal constitutionalism. The analysis of the possible clash between the two legal agendas focuses on the independence of the judiciary that has been severely undermined in Hungary and Poland, and that also constitutes a clash with the rule of law as interpreted in the European context. A clash that would allow measures to be taken against the state in question, however, is difficult to determine.
Keywords: rule of law, international law, European law, international institutions, populist radical right